Fabrication of Charcoal from Jackfruit’s Peel (Artocarpus heterophyllus) as Adsorbent on Dissolved Cadmium and Nickel - Baloga, Hendra; Walanda, Daud K; Hamzah, Baharuddin (Universitas Tadulako, 2019)
Jackfruit’s peel contains lignocellulosic compounds that potential for fabrication of charcoal and useful for adsorbing heavy metals. Based on this, then it was conducted a study on the utilization of charcoal from jackfruit’s peel to be used as adsorbent on cadmium and nickel. The analysis process of this research was conducted by using atomic absorption spectrophotometry (SSA). The results showed that charcoal’s characteristics from jackfruit’s peel contained of 4.4% water, 9.3% ash, and biomass content that can be used as an absorbent was 86.3%. The optimum adsorption of charcoal from jackfruit’s peel for cadmium ion was contact time of 120 minutes, pH 7 and concentration of 40 mg/L with the percentages of penetration respectively were 84.65%, 99.10%, and 99.43%. On the other hand, for nickel was 150 minutes of contact time, pH 5, and concentration of 20 mg/L with percentage of penetration were 87.95%, 91.75%, and 75.15% respectively.